Valproic Acid Decreases the Nuclear Localization of MDT-28, the Nematode Orthologue of MED28 - Kostrouchová, M; Kostrouchová, V; Yilma, P; Benda, A; Mandys, V; Kostrouchová, M (Folia biologica, 2018)
Mediator is a multiprotein complex that connects regulation mediated by transcription factors with RNA polymerase II transcriptional machinery and integrates signals from the cell regulatory cascades with gene expression. One of the Mediator subunits, Mediator complex subunit 28 (MED28), has a dual nuclear and cytoplasmic localization and function. In the nucleus, MED28 functions as part of Mediator and in the cytoplasm, it interacts with cytoskeletal proteins and is part of the regulatory cascades including that of Grb2. MED28 thus has the potential to bring cytoplasmic regulatory interactions towards the centre of gene expression regulation. In this study, we identified MDT-28, the nematode orthologue of MED28, as a likely target of lysine acetylation using bioinformatic prediction of posttranslational modifications. Lysine acetylation was experimentally confirmed using anti-acetyl lysine antibody on immunoprecipitated GFP::MDT-28 expressed in synchronized C. elegans. Valproic acid (VPA), a known inhibitor of lysine deacetylases, enhanced the lysine acetylation of GFP::MDT-28. At the subcellular level, VPA decreased the nuclear localization of GFP::MDT-28 detected by fluorescencelifetime imaging microscopy (FLIM). This indicates that the nuclear pool of MDT-28 is regulated by a mechanism sensitive to VPA and provides an indirect support for a variable relative proportion of MED28 orthologues with other Mediator subunits.
Keywords: lysin; transport proteinů; Valproic Acid; Humans; Recombinant Fusion Proteins; sekvenční homologie aminokyselin; zelené fluorescenční proteiny; Cell Nucleus; Sequence Homology, Amino Acid; Lysine; Protein Transport; larva; Acetylation; acetylace; Green Fluorescent Proteins; mediátorový komplex; jaderné proteiny; buněčné jádro; lidé; Densitometry; zvířata; Caenorhabditis elegans; Caenorhabditis elegans Proteins; výpočetní biologie; Amino Acid Sequence; proteiny Caenorhabditis elegans; Computational Biology; Nuclear Proteins; rekombinantní fúzní proteiny; Larva; denzitometrie; Animals; Mediator Complex; kyselina valproová; sekvence aminokyselin